Arterial Blood Pressure at Liver Transplant Evaluation Predicts Renal Histology in Candidates With Renal Dysfunction. Issue 12 (31st October 2019) - Wadei, Hani M.; Abader, Peter; Alsaad, Ali A.; Croome, Kristopher; Cortese, Cherise; Geiger, Xochiquetzal J.; Khouzam, Samir; Mai, Martin L.; Taner, C. Burcin; Keaveny, Andrew P.
Abstract : Renal dysfunction is common in liver transplantation (LT) candidates, but differentiating between reversible and irreversible renal injury can be difficult. Kidney biopsy might be helpful in differentiating reversible from irreversible renal injury, but it is associated with significant complications. We aimed to identify pre‐LT predictors of potentially reversible renal injury using histological information obtained on pre‐LT renal biopsy. Data on 128 LT candidates who underwent pre‐LT kidney biopsy were retrospectively collected and correlated with renal histological findings. Indications for kidney biopsy were iothalamate glomerular filtration rate (iGFR) ≤40 mL/minute, proteinuria >500 mg/day, and/or hematuria. According to the biopsy diagnosis, patients were grouped into the following categories: normal (n = 13); acute tubular necrosis (ATN; n = 25); membranoproliferative glomerulonephritis (n = 19); minimal histological changes (n = 24); and advanced interstitial fibrosis (IF) and glomerulosclerosis (GS) (n = 47). Compared with patients having advanced IF/GS, patients with normal biopsies and those with ATN had lower systolic blood pressure (SBP) and diastolic blood pressure (DBP) and higher international normalized ratio and total bilirubin levels (<0.05 for all). Both SBP and DBP directly correlated with the degree of IF and GS ( R  = 0.3, P  ≤ 0.02 for all). SBP ≤90 mm Hg was 100% sensitive and 98% specific in correlating with normal biopsies or ATN, whereas SBP ≥140 mm Hg was 22% sensitive and 90% specific in correlating with advanced IF/GS. Model for End‐Stage Liver Disease score, serum creatinine, iGFR, urinary sodium excretion, and renal size did not correlate with biopsy diagnosis or degree of IF or GS. In conclusion, SBP at the time of LT evaluation correlates with renal histology, and it should be included along with other clinical and laboratory markers in the decision‐making process to list patients with renal dysfunction for LT alone versus simultaneous liver‐kidney transplantation.